The Influence Of Advertising And Sales Promotion On Purchasing Decisions At Gultik Stores In Balikpapan City - Syarifa Badria; Ramli Ramli; Iwan Adinugroho (Jurnal Indonesia Sosial Teknologi, 2023)
Individual Gultik Shop in Balikpapan City. This type of food is very popular among young people in Jakarta, and this food needs to be further developed and served among young people in the city of Balikpapan. How to introduce Gultik Rakyat is also simple. Gultik Rakyat is a food made from hamburger curry which is then made by boiling until cooked, then the meat is cut into small pieces then the meat is blended with gravy that is suitable for serving by buyers. The testing technique used is a quantitative method with important information taken using polls, the number of residents who are respondents are buyers who have bought groceries at Toko Gultik Rakyat. In the results of various straight relapse investigations, the direction of a positive relationship is seen from the value of a positive relationship coefficient, then the large value of the driving variable is SIG. 0.002 < 0.05 and tcount of 4.008 > ttable of 1.661. Promote variables to specific GIs. 0.004 < 0.05 and tcount of 3.884 > ttable of 1.661. In the F esteem test, it was found that Fcalculate esteem was 32.190 with an importance value of 0.000 and critical F esteem < 0.05. As a result, H0 is rejected and Ha is recognized. That is, the independent factors of publication (X1) and transaction progress (X2) act simultaneously or together on the dependent variable on the purchase option (Y). Meanwhile, judging from the results of the connection test, it was found that the relationship coefficient (R Square) is 0.425, and this means that the relationship between promotion and promotion factors on the purchase choice variable is strong.